Iman Cognitive Therapy (ICT) Sebagai Model Peningkatan Resiliensi Mahasiswa Poltekkes Kemenkes Yogyakarta - Sarka Ade Susana; Yusniarita Yusniarita (Poltekkes Kemenkes Bengkulu, 2022)
Stressors that cause problems cannot be avoided in the lives of everyone. Student life especially in the Health Polytechnic of Health Ministry Yogyakarta and more specifically in those who live in the Dormitory as well. Those who are educated to become health workers later, are demanded not only to be able to provide services or health assistance for others, but more fundamentally is able to deal with and solve their own problems. Those in front of people who need health services are like people without problems and for this reason since the process of education requires the ability and resilience to deal with and solve problems independently. For this reason this research was carried out, so it is expected that with Iman Cognitive Therapy (ICT) they have a high level of resilience. This study was designed with quasi-experiment with pre post test with control group design. Using cluster random sampling with 88 samples divided into 44 treatment samples in dormitories one and 44 samples in dormitories Two and three.Data collected with Qutionare pre and post ICT. Analysis data used univariate dan bivariate T-test. The results of this study get the level of resilience of respondents before and after ICT with a score of 53.5 and 54.6 for the control group (medium-moderate category), for the treatment group 52.8 and 70.9 (medium-high category). After independent sample t-test between the difference between the pre-post control group and the difference between the pre-post treatment group obtained p-value: 0,000, which means there is a difference in value between the control group and the treatment group. Thus it can be concluded that ICT has a significant impact on increasing the resilience of students living in the dormitory of Health Polytechnic of Health Ministry Yogyakarta.